Polyethyleneimine/sodium dodecyl sulphate adsorbed silica particles and their adsorption properties - Sorapong Janhom (2018)
Silica particles were modified in aqueous solution with polyethyleneimine (PEI) and sodium dodecyl sulphate (SDS), in order to introduce a hydrophobic surface on the silica particles. The properties of adsorbed layers have been explored using spectrophotometry and the factors affecting PEI adsorption on silica particles, such as material liquor ratios (MLR), PEI concentration, pH in the range of 3-12 and electrolyte concentration of 0-0.100M NaCl. The PEI adsorption on silica particles at various pHs indicated that the adsorbed amount of PEI increased with pH. The influence of NaCl on PEI adsorption revealed that increasing NaCl concentration decreased the absorbed amount of PEI. The adsorption of SDS on PEI-modified silica particles was then investigated using nephelometry. The influence of NaCl and pH on SDS adsorption on the PEI-modified silica particles was also studied. The increasing NaCl concentration decreased the adsorbed amount of SDS. The SDS adsorption at various pH indicated that the adsorbed amount of SDS increased with the decrease in pH. In addition, the surface charge of the PEI-modified and PEI/SDS-modified silica particles were investigated via zeta potential measurements. The Langmuir adsorption isotherm of the soybean oil on the PEI-modified silica particles with corresponding was determined. The oil sorption amount on the PEI-modified and PEI-SDS-modified silica particles were increased in comparison to the unmodified silica surface with the highest adsorbed amounts of soybean oil of a 2goil/gsilica. The size and morphology of the resulting particles were examined by polarizing microscope and stereo microscope. © 2010 Elsevier B.V.